Question
upstudy study bank question image url

Find the derivative of the given function. \[ y=\left(2 x^{2}-8 x\right) e^{-8 x} \]

Ask by Reed Watson. in the United States
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of the function \( y = (2x^2 - 8x)e^{-8x} \) is: \[ y' = (-16x^2 + 68x - 8)e^{-8x} \] \end{Output}

Solution

Alright, I need to find the derivative of the function \( y = (2x^2 - 8x)e^{-8x} \). Let's break this down step by step to ensure I cover all possible angles and methods. First, I recognize that this is a product of two functions: \( u(x) = 2x^2 - 8x \) and \( v(x) = e^{-8x} \). To find the derivative of their product, I'll use the product rule, which states that if \( y = u(x)v(x) \), then \( y' = u'(x)v(x) + u(x)v'(x) \). So, let's find the derivatives of \( u(x) \) and \( v(x) \) individually. 1. **Finding \( u'(x) \):** \( u(x) = 2x^2 - 8x \) - The derivative of \( 2x^2 \) with respect to \( x \) is \( 4x \). - The derivative of \( -8x \) with respect to \( x \) is \( -8 \). - Therefore, \( u'(x) = 4x - 8 \). 2. **Finding \( v'(x) \):** \( v(x) = e^{-8x} \) - The derivative of \( e^{kx} \) with respect to \( x \) is \( ke^{kx} \), where \( k \) is a constant. - Here, \( k = -8 \), so \( v'(x) = -8e^{-8x} \). Now, applying the product rule: \[ y' = u'(x)v(x) + u(x)v'(x) \] Substituting the derivatives we found: \[ y' = (4x - 8)e^{-8x} + (2x^2 - 8x)(-8e^{-8x}) \] Let's simplify this expression step by step. First, distribute the terms: \[ y' = (4x - 8)e^{-8x} - 8(2x^2 - 8x)e^{-8x} \] \[ y' = (4x - 8)e^{-8x} - 16x^2e^{-8x} + 64xe^{-8x} \] Now, combine like terms: \[ y' = (4x - 8 - 16x^2 + 64x)e^{-8x} \] \[ y' = (-16x^2 + 68x - 8)e^{-8x} \] To make it more readable, I can factor out a common factor of \( -8 \) from the polynomial: \[ y' = -8(2x^2 - 8.5x + 1)e^{-8x} \] Alternatively, if I prefer to keep it in the expanded form: \[ y' = (-16x^2 + 68x - 8)e^{-8x} \] Both forms are correct, but the factored form might be more useful depending on the context or further simplification needed. **Double-Checking:** To ensure there are no mistakes, I'll verify the derivative by plugging in a value for \( x \) and checking if the derivative makes sense. Let's choose \( x = 1 \): \[ u(1) = 2(1)^2 - 8(1) = 2 - 8 = -6 \] \[ v(1) = e^{-8(1)} = e^{-8} \approx 0.000335 \] \[ u'(1) = 4(1) - 8 = 4 - 8 = -4 \] \[ v'(1) = -8e^{-8} \approx -8 \times 0.000335 \approx -0.00268 \] \[ y'(1) = (-4)(0.000335) + (-6)(-0.00268) \approx -0.00134 + 0.01608 \approx 0.01474 \] Calculating the derivative using the expanded form: \[ y'(1) = (-16(1)^2 + 68(1) - 8)e^{-8} = (-16 + 68 - 8)e^{-8} = 44e^{-8} \approx 44 \times 0.000335 \approx 0.01474 \] The results match, confirming that the derivative is correctly calculated. **Alternative Approach:** Another way to approach this problem is by using logarithmic differentiation, which can be particularly useful for products and quotients of functions. Starting with: \[ y = (2x^2 - 8x)e^{-8x} \] Take the natural logarithm of both sides: \[ \ln(y) = \ln(2x^2 - 8x) + \ln(e^{-8x}) = \ln(2x^2 - 8x) - 8x \] Differentiate both sides with respect to \( x \): \[ \frac{1}{y} \cdot y' = \frac{4x - 8}{2x^2 - 8x} - 8 \] Multiply both sides by \( y \): \[ y' = y \left( \frac{4x - 8}{2x^2 - 8x} - 8 \right) \] Substitute \( y = (2x^2 - 8x)e^{-8x} \): \[ y' = (2x^2 - 8x)e^{-8x} \left( \frac{4x - 8}{2x^2 - 8x} - 8 \right) \] Simplify the expression inside the parentheses: \[ \frac{4x - 8}{2x^2 - 8x} = \frac{4(x - 2)}{2x(x - 4)} = \frac{2(x - 2)}{x(x - 4)} \] So, \[ y' = (2x^2 - 8x)e^{-8x} \left( \frac{2(x - 2)}{x(x - 4)} - 8 \right) \] This approach leads to the same derivative as the product rule method, confirming the result. **Conclusion:** After applying both the product rule and logarithmic differentiation, the derivative of the function \( y = (2x^2 - 8x)e^{-8x} \) is: \[ y' = (-16x^2 + 68x - 8)e^{-8x} \] This derivative accurately represents the rate of change of the original function with respect to \( x \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the derivative of the function \( y = \left(2x^{2} - 8x\right) e^{-8x} \), we will use the product rule. The product rule states that if you have a function that is the product of two functions, \( u \) and \( v \), the derivative \( y' \) is given by: \[ y' = u'v + uv' \] Here, let: - \( u = 2x^{2} - 8x \) - \( v = e^{-8x} \) Now, we need to find the derivatives \( u' \) and \( v' \). 1. For \( u = 2x^{2} - 8x \): \[ u' = 4x - 8 \] 2. For \( v = e^{-8x} \): Using the chain rule, we find: \[ v' = e^{-8x} \cdot (-8) = -8e^{-8x} \] Now, applying the product rule: \[ y' = (4x - 8)e^{-8x} + (2x^{2} - 8x)(-8e^{-8x}) \] Factor out \( e^{-8x} \): \[ y' = e^{-8x} \left[(4x - 8) - 8(2x^{2} - 8x)\right] \] Now simplify the expression inside the brackets: \[ = e^{-8x} \left[4x - 8 - 16x^{2} + 64x\right] \] Combine like terms: \[ = e^{-8x} \left[-16x^{2} + 68x - 8\right] \] Thus, the derivative of the function is: \[ y' = e^{-8x} (-16x^{2} + 68x - 8) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy